GENDER DAN ISLAM - Emawati Emawati (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
Gender in a glance is often trigger debate to explain it because of a superficial comprehension. Some people also think thatthe term gender appears only among liberalism. Actually, term gender has emerged at the time of the Prophet. This condition has beendescribed by the Qur'an. In the Qur'an, there’s perceived justice between men and women. However, the interpretation, there are genderverses, which place women in subordinate position so that it will make women cornered. This paper describes about the Islamic view ofwomen in reality to reach equality with men